2016
DOI: 10.1021/acs.jafc.6b01699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Herbicide Imazethapyr on Photosynthesis in PGR5- and NDH-DeficientArabidopsis thalianaat the Biochemical, Transcriptomic, and Proteomic Levels

Abstract: Photosynthesis is a very important metabolic pathway for plant growth and crop yield. This report investigated the effect of the herbicide imazethapyr on photosynthesis in the Arabidopsis thaliana pnsB3 mutant (a defect in the NDH pathway) and pgr5 mutant (a defect in the PGR5 pathway) to determine which cyclic electron transport chain (CET) of the NDH and PGR5 pathways is more important for protecting the photosynthetic system under herbicide stress. The results showed that 20 μg/L imazethapyr markedly inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 46 publications
(83 reference statements)
2
20
0
Order By: Relevance
“…In another study, exposure of A. thaliana plants to trace concentration of imazethapyr strongly affected chlorophyll synthesis and increased reactive oxygen species (ROS) (Qian et al, 2011 , 2015 ). Short exposure of rice seedlings to imazethapyr induced damages to lipid membranes and negatively affected the transcription of a number of genes involved photosynthesis, starch and sugar metabolism, and the tricarboxylic acid cycle (Qian et al, 2011 ; Sun et al, 2016 ). Cheng et al ( 2013 ) and Li et al ( 2015 ) also found that, at the vacuolated-microspore stage of MES-treated rapeseed anther, the chloroplasts in the epidermis and endothecium cells exhibited defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study, exposure of A. thaliana plants to trace concentration of imazethapyr strongly affected chlorophyll synthesis and increased reactive oxygen species (ROS) (Qian et al, 2011 , 2015 ). Short exposure of rice seedlings to imazethapyr induced damages to lipid membranes and negatively affected the transcription of a number of genes involved photosynthesis, starch and sugar metabolism, and the tricarboxylic acid cycle (Qian et al, 2011 ; Sun et al, 2016 ). Cheng et al ( 2013 ) and Li et al ( 2015 ) also found that, at the vacuolated-microspore stage of MES-treated rapeseed anther, the chloroplasts in the epidermis and endothecium cells exhibited defects.…”
Section: Discussionmentioning
confidence: 99%
“…Both amidosulfuron (Figure 3 ) and MES exposure (Li et al, 2015 ) led to decrease in soluble sugars content in leaf and flower bud, and therefore, it was assumed that carbohydrate metabolism maybe blocked in these treatments. Moreover, the results of Sun et al ( 2016 ) showed that A. thaliana cultivated in a solution containing 20 μg/L imazethapyr produced more anthocyanins and ROS, particularly in the pgr5 mutant (a defect in the proton gradient regulation 5 pathway). Their results also showed that the PSII was severely damaged and the transcript levels of most photosynthesis-related genes were decreased in the treated plants (Sun et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As oxidative stress increases, there is a cascade reaction with increased lipid peroxidation, membrane damage, protein damage, especially ATP synthase and vacuolar ATPase (V-ATPase), nucleic acids and thylakoids, which lose their ability to perform photosynthesis (Neilson et al, 2010). The application of herbicides leads to changes in photosynthesis and the increase of ROS in peanut, arabidopsis, rice and wheat plants (Agostinetto et al, 2016;Nohatto et al, 2016;Radwan and Fayez, 2016;Sun et al, 2016).…”
mentioning
confidence: 99%